2014
DOI: 10.1007/s13187-014-0751-6
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Immigrant and Refugee Women in Breast Health Education

Abstract: This project assessed the impact of a community-based educational program on breast cancer knowledge and screening among Buffalo (NY) immigrant and refugee females. Program participants completed language-matched pre- and post-test assessments during a single session educational program; breast cancer screening information was obtained from the mobile mammography unit to which participants were referred. Pre- and post-test knowledge scores were compared to assess changes in responses to each of the six individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 19 publications
0
52
0
Order By: Relevance
“…Patient navigation services have also been shown to increase screening rates, though these services are unavailable in most healthcare settings. In addition, encouraging preventative health visits and increased contact with the healthcare system has been correlated with increased cancer screenings (Gondek et al, 2015;Brown, Consedine & Magai 2006;Percac-Lima,Ashburner, Bond, Oo & Atlas, 2013).…”
Section: Breast Cancer Screeningmentioning
confidence: 99%
“…Patient navigation services have also been shown to increase screening rates, though these services are unavailable in most healthcare settings. In addition, encouraging preventative health visits and increased contact with the healthcare system has been correlated with increased cancer screenings (Gondek et al, 2015;Brown, Consedine & Magai 2006;Percac-Lima,Ashburner, Bond, Oo & Atlas, 2013).…”
Section: Breast Cancer Screeningmentioning
confidence: 99%
“…A combination of personal determinants such as low selfefficacy, low knowledge, high perceived barriers, and low perceived susceptibility; and environmental factors such as low awareness of physicians regarding the severity of metastatic breast cancer among refugee women, lack of health literate and culturally competent educational skills, and issues related to the local healthcare system (unavailability of funding for chronic disease screening and treatment for refugees, high costs of medical services, lack of properly educated nurses, and lack of transportation means from camps to hospitals) have been negatively affecting screening and chemotherapy completion rates among the target population (1,3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Aside from the lack of funding allocated by the main refugee organization in the country, United Nations High Commissioner for Refugees (UNHCR), the absence of human right policies at the societal level to protect the integrity of refugees and ensure the equitable receival of urgent medical care by disadvantaged populations amidst prevailing political corruption has worsened mammography and treatment rates by contributing to the stigma associated with e refugee status in the host community (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…[15,18,27,28] Breast cancer screening was higher in our study than what was observed in research conducted in Buffalo, New York (54% vs 35%). [29] This study bears similarities to ours because it included the same culture groups and focused on never screened and not up-to-date participants. The difference in completion proportions between the studies may be explained by the type of education and assistive services offered.…”
Section: Plos Onementioning
confidence: 98%
“…Other studies among never screened resulted in refugee women in Buffalo (NY) following a community-based educational program, 20 of 58 (34%) women received a mammogram who had never completed a mammogram screening before intervention. [29] United States domestic screening requirements for arriving refugees mandate refugees to have Hepatitis B Virus (HBV) screening. [33] However, few of our participants recalled a prior testing, nor could they verify their HBV status at the time of enrollment (69% did not know their status).…”
Section: Plos Onementioning
confidence: 99%